PENGARUH HARGA DAN PERSEPSI KUALITAS TERHADAP MINAT PEMBELIAN ULANG PADA UMKM PECAH BELAH YENI JAPANG - Candrianto Candrianto; Yeni Arlinda (Politeknik ATI Padang, 2018)
This study aims to determine the effect of prices and perceived quality on the interest in repurchasing Yeni Japang SME. This research is a causative study with quantitative methods. The sample used in this study were 100 respondents. The results showed that the price had a negative but not significant effect on the intention to repurchase Yeni Japang split MSMEs. This means that if the price of a glass plate increases, the interest in repurchasing decreases or vice versa. This product is very sensitive to price changes. Further perceptions of quality have a significant positive effect on repurchase interest. This means that the customer has a high perception of product quality, it will arouse the interest of customers to repurchase. Perception of quality is one of the determinants of whether a customer will buy a product or not.